Effects of photoperiod with blue and red led on functional properties of Lactuca sativa cv. fire red under controlled environment / Emmelly Imbuh Ngilah - Ngilah, Emmelly Imbuh (2019)
Application of Light Emitting Diode (LED) in agricultural sector has recently been studied for indoor vegetable and ornamental plants as a supplemental light source. Several studies had been carried out by researchers to explore the appropriate light spectrum for the optimum growth of specific plant species, especially the high values crops, under controlled environment. This current research work was, hence, conducted to determine the effects of narrowed wavelength of Red (R) LED and Blue (B) LED, and their combinations at 1:1, 1:2 and 2:1, at 18W and 240V, on production of Lactuca sativa cv. Fire Red (lettuce) in laboratory at total absence of natural light. Each LED irradiation treatment was assigned as sub plot with photoperiods (PPs) ranging from 12 h to 18 h as main plots in a split plot design to study their combined effects on the growth, pigment and ascorbic acid contents of this attractive red colour vegetable.